2012
DOI: 10.1037/a0029774
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between personal characteristics, multicultural attitudes, and self-reported multicultural competence of graduate students.

Abstract: This study examined some of the underlying attitudes and psychological factors that may affect the self-reported multicultural competence of counseling professionals. Two subscales of the Personality Research Form, the Rosenberg Self-Esteem Scale, two subscales of the Sixteen Personality Factor Questionnaire (16PF), the Quick Discrimination Index subscales, and the Multicultural Counseling Knowledge and Awareness Scale were administered to 129 graduate students in counseling. Results of regression analyses ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
24
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(30 citation statements)
references
References 31 publications
5
24
1
Order By: Relevance
“…The current study replicated and expanded upon the Reynolds and Rivera () study. Our hypotheses were partially supported: Similar to the Reynolds and Rivera () study, we found that cognitive racial attitudes significantly predicted MCC awareness and that neither openness nor race/ethnicity predicted awareness or knowledge. However, in contrast to our hypotheses and the findings from Reynolds and Rivera (), we found that cognitive racial attitudes did not predict MCC knowledge.…”
Section: Discussionsupporting
confidence: 57%
See 4 more Smart Citations
“…The current study replicated and expanded upon the Reynolds and Rivera () study. Our hypotheses were partially supported: Similar to the Reynolds and Rivera () study, we found that cognitive racial attitudes significantly predicted MCC awareness and that neither openness nor race/ethnicity predicted awareness or knowledge. However, in contrast to our hypotheses and the findings from Reynolds and Rivera (), we found that cognitive racial attitudes did not predict MCC knowledge.…”
Section: Discussionsupporting
confidence: 57%
“…Although we did not find a predictive relationship between multicultural training and MCC knowledge, we did find that multicultural training predicted MCC awareness. Given the demographic similarity between studies, the different results likely stemmed from Reynolds and Rivera () using a different measure of MCC—the Multicultural Counseling Knowledge and Awareness Scale (MCKAS; Ponterotto, Gretchen, Utsey, Rieger, & Austin, ). The MCKAS has items that assess more specific MCC knowledge (e.g., “I am aware some research indicates that minority clients are more likely to be diagnosed with mental illness than are majority clients”) than CBMCS items (e.g., “I have an excellent ability to critique multicultural research”), and this specificity is potentially more activating for individuals with lower cognitive racial attitudes (i.e., more biased toward racial and ethnic minorities).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations